STUDI DESKRIPTIF KEMAMPUAN KOMUNIKASI TULIS DALAM MENYELESAIKAN SOAL PECAHAN CAMPURAN PADA PESERTA DIDIK KELAS VII SMPN 1 LAMPASIO - Musfira; Fitria; Nursupiamin (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
Communication skills are important for every human being. Communication in this study focused on the written communication skills of students in solving mixed fraction questions. This quantitative descriptive research was conducted at SMPN 1 Lampasio, Tolitoli Regency, Central Sulawesi with the object of research as many as 15 grade VII students in the odd semester of the 2020/2021 school year. The data collection technique used was the test method to obtain data on the written communication skills of mixed fraction material. Based on the results of the study, it shows that 7% of the 15 research objects have written communication skills, including in the low ability category, 86% in the medium ability category, and 7% in the high ability category. The characteristics of the test results show that students who have written communication skills in the low category generally only remember the material or memorize but are weak in the aspect of understanding the material. Meanwhile, students who have written communication skills in the medium category show that the stages are already able to write answers close to perfect where the direction of the answer structure and solving strategies used is visible, but there are still errors in the accuracy and correctness of the answers. And for students who have written communication skills in the high category show the ability to use mathematical language, the solving strategies used, the accuracy and correctness of answers, and the answer structure is perfect